Association of Area Deprivation Index with Adherence to Proposed Regimen in Patients with Sarcoidosis in Detroit, Michigan - Cherabuddi, Medha R; Goodman, Benjamin; Ayyad, Asem; Almajali, Dina A; Nadeem, Owais; Bradley, Patrick; Russell, Cori; Ouellette, Daniel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Social predictors affect severity of sarcoidosis, with Black patients, older individuals, those with lower income, and those without insurance having greater severity. This study aimed to explore potential disparities affecting access to care in sarcoidosis patients with a primary focus on metrics such as area deprivation index (ADI) and its association with adherence to the proposed regimen.Methods: A retrospective chart review study of all patients seen in pulmonary clinics at a large urban tertiary care center over 2 years with sarcoidosis patients identified with International Classification of Diseases diagnosis code D86. Data collected included age, race, sex, ADI, insurance, online patient portal usage, chest x-rays, pulmonary function tests, missed visits, hospitalizations, positive biopsy, communication and visits around bronchoscopy. Categorical variables were described using frequency and percentage. Numerical variables were described using median, mean and standard deviation. Statistical analysis included chi-square test, two-sample T-test and Wilcoxon rank sum test. Multivariate logistic regression analysis was performed to model independent association with 12 month no-show occurrence as a metric of adherence to the proposed regimen.Results: Among sarcoidosis patients (N = 788), univariate models showed the presence of active online patient portal use among younger patients (58.6 years with portal vs. 65.1 years without portal, p < 0.001), those with lower ADI (73 with portal vs. 92 without portal, p < 0.001) and with commercial insurance (48.5% with portal vs. 20.7% without portal, p < 0.001); more x-rays (45.6% with x-rays vs. 36.6% without x-rays, p = 0.018) and hospitalizations (50.3% with hospitalizations vs. 36.2% without hospitalizations, p < 0.001) in Medicare patients. Sarcoidosis patients with positive biopsies on file from 2013-2023 were more likely to be male (44.19% with positive biopsy vs. 33.91% without positive biopsy, p = 0.006), White (36.29% with positive biopsy vs. 22.9% without positive biopsy, p < 0.001) or other races (3.23% with positive biopsy vs. 2.25% without positive biopsy, p < 0.001), younger (55.8 years with positive biopsy vs. 61.7 years without positive biopsy, p < 0.001) and belonged to lower national ADI ranks (73 with positive biopsy vs. 80 without biopsy, p = 0.041). A multivariate analysis was done with those variables found to be significant in the univariate analyses, which revealed that higher ADI national was associated with failure to adhere to the proposed regimen.Conclusions: We identified intricate patterns of sociodemographic variables affecting access to care in sarcoidosis patients, especially higher ADI national associated with failure to adhere to the proposed regimen, raising concerns for potential healthcare barriers. Understanding these barriers is vital for equitable high-quality care, assisting in timely and efficient management of the patient’s disease.